Relationship Between Mental Health and Student Learning Outcomes at JHS 01 in Bongan District, West Kutai Regency - Bakrul Ali, Ahmad; Rasmun, Rasmun; Rahman, Gajali (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: In the era of globalization, the world of education in psychology is increasingly known by the Indonesian people. Psychological approach as an effort to find solutions to various problems faced by humans is a very wise choice. Psychology aims to grow and develop Community Mental Health, one of which is through education. Objective: To determine the relationship between mental health and student learning outcomes at JHS 01 in Bongan District, West Kutai Regency. Methods: The research design in this study was descriptive correlation using a cross-sectional approach. The study was conducted in March 2022. The population in this study were all students of JHS 1 Bongan in Bongan District, West Kutai Regency in 2022 totaling 116 people. The statistical test used is Chi-Square if it is obtained t arithmetic (p-value) <0.05, then the hypothesis Ha is accepted and Ho is rejected. Result and Discussion: The relationship between mental health and student learning outcomes (pValue = 0.00). Mental health at JHS 01 Bongan is in the sufficient category (52.6%). Student learning outcomes at JHS 01 Bongan are in the satisfactory category (38.8%). Conclusion: the relationship between mental health and student learning outcomes at JHS 01 in Bongan District, West Kutai Regency.